2010
DOI: 10.1140/epjb/e2010-00089-2
|View full text |Cite
|
Sign up to set email alerts
|

Percolation of aligned dimers on a square lattice

Abstract: Percolation and jamming phenomena are investigated for anisotropic sequential deposition of dimers (particles occupying two adjacent adsorption sites) on a square lattice. The influence of dimer alignment on the electrical conductivity was examined. The percolation threshold for deposition of dimers was lower than for deposition of monomers. Nevertheless, the problem belongs to the universality class of random percolation. The lowest percolation threshold (pc = 0.562) was observed for isotropic orientation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 40 publications
(50 reference statements)
12
43
0
Order By: Relevance
“…Numerous practical problems include conductivity in composite materials, flow through porous media, polymerization, and behavior of scale-free random networks such as the Internet [4]. The problem of percolation is not a new one but still attracts considerable interest [5][6][7][8][9][10][11][12][13][14][15][16], and some unsolved questions remain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous practical problems include conductivity in composite materials, flow through porous media, polymerization, and behavior of scale-free random networks such as the Internet [4]. The problem of percolation is not a new one but still attracts considerable interest [5][6][7][8][9][10][11][12][13][14][15][16], and some unsolved questions remain.…”
Section: Introductionmentioning
confidence: 99%
“…6 12 6 0.6695 (7) 0.5836 (11) used to obtain the dependence of the percolation threshold in polydisperse composites on the dispersion. However, not much is known about the influence of the particle size dispersion on the properties of composite materials and there are still many questions to be answered.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most of the studies are devoted to the percolation of objects whose size coincides with the size of the lattice site (single occupancy). However, if some sort of correlation exists, like particles occupying several k contiguous lattice sites (k-mers), the statistical problem becomes exceedingly difficult and a few studies have been devoted to understanding the percolation of elements occupying more than one site (bond) [6,7,8,9,10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As for cases of continuum percolation models, a simulation study showed 10) that even simpler size distributions (Gaussian, uniform, and log-normal distributions of particles, regardless of their conductivity) shows a clearly nontrivial effect. Even in simpler models, 11,12) for example, conductor sites arranged in length X bars aligned vertically or horizontally in square lattice, 13) can exhibit quite complex effects and there actually is an optimum value of X, beyond which the effect on p c is inversed.…”
Section: Introductionmentioning
confidence: 99%